Man and His Mind-Changers
102 p.
Keywords: "We ourselves are part of the problem, not ofits solution". This pronouncement, made by psychologist R. S. B. Wiener during the panel on social policy, provided a leading Dutch weekly with an excellent headline for an article on the 30th International Congress on Alcoholism and Drug Dependence. With it Wiener touched one of the central, if not the central issue of the alcohol and drug problem. Why do we fix our attention so emphatically on 'the other people', on the consumers, abusers and addicts? Has not the time come that, also at scientific and learned congresses, we should start occupying ourselves with the shortcomings of society and with its legislation and policy as factors promoting this abuse and addiction? The question is so obvious that no one will dare give a neg ative answer. For this reason it is even more striking that it is given so little serious thought. We still try to change the consumer instead of the social structure. In his opening address, the Minister of Public Health and Environmental Hygiene of the Netherlands, Dr 1. B. J. Stuyt, gave some attention to this social structure. He pointed out that a social structure which is characterized by poverty and deprivation promotes the abuse of alcohol. Dekker/van der Wal (eds. ). Man and His Mind-Changers. 1-9. All Rights Reserved. Copyright © 1973 by D. Reidel Publishing Company. Dordrecht-Holland 2 E. DEKKER AND H. J.